2019
DOI: 10.1016/j.jss.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Fine-grained just-in-time defect prediction

Abstract: Defect prediction models focus on identifying defect-prone code elements, for example to allow practitioners to allocate testing resources on specific subsystems and to provide assistance during code reviews. While the research community has been highly active in proposing metrics and methods to predict defects on long-term periods (i.e., at release time), a recent trend is represented by the so-called short-term defect prediction (i.e., at commit-level). Indeed, this strategy represents an effective alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(84 citation statements)
references
References 74 publications
1
82
1
Order By: Relevance
“…Such code changes (or commits) must undergo rigorous SQA activities (e.g., Continuous Integration tests and code review) prior to merge into the main branch (e.g., a master branch) [24]. Since these commit-level SQA activities are time-consuming, Just-In-Time defect prediction has been proposed to support developers by prioritizing their limited SQA effort on the most risky code changes that will introduce software defects during the development cycle (i.e., pre-release defects) [45,61]. Nevertheless, JIT defect prediction only early detects defect-inducing changes, rather than post-release defects (i.e., the areas of code that are likely to be defective after a release).…”
Section: Sqa Activities During the Development Stagementioning
confidence: 99%
See 2 more Smart Citations
“…Such code changes (or commits) must undergo rigorous SQA activities (e.g., Continuous Integration tests and code review) prior to merge into the main branch (e.g., a master branch) [24]. Since these commit-level SQA activities are time-consuming, Just-In-Time defect prediction has been proposed to support developers by prioritizing their limited SQA effort on the most risky code changes that will introduce software defects during the development cycle (i.e., pre-release defects) [45,61]. Nevertheless, JIT defect prediction only early detects defect-inducing changes, rather than post-release defects (i.e., the areas of code that are likely to be defective after a release).…”
Section: Sqa Activities During the Development Stagementioning
confidence: 99%
“…The cost-effectiveness of the SQA resource prioritization heavily relies on the granularity levels of defect prediction. Prior studies argued that prioritizing software modules at the finer granularity is more cost-effective [28,43,61]. For example, Kamei et al [43] found that the file-level defect prediction is more effective than the package-level defect prediction.…”
Section: The Granularity Levels Of Defect Predictions Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the software change, the researchers have proposed the change‐level defect prediction, which is known as just‐in‐time defect prediction [23, 24]. Unlike the traditional defect prediction methods, the change‐level defect prediction methods regard a change as an instance for training and predict whether new software changes introduce changes or not.…”
Section: Related Workmentioning
confidence: 99%
“…Considering a commit in the software development may be partially defective, which may involve defective files and nondefective files. To this end, Pascarella et al [23] proposed a fine-grained JIT-SDP model to predict buggy files in a commit based on ten open-source projects. Experimental results show that 43% defective commits are mixed by buggy and clean resources, and their method can obtain 82% AUC-ROC to detect defective files in a commit.…”
Section: Background and Related Workmentioning
confidence: 99%